financing the state budget in Syria through the issuance of government securities (Journal of Hama University, 2021)
The aim of this research is to analyze the current reality of financing the state’s general budget in Syria, and to assess the Syrian experience in issuing government securities, leading to an indication of the prospects for the process of issuing government securities in post-war Syria.The research relied on the descriptive and analytical approach based on statistics, reports and studies published in the field of research, as this approach was used to determine the characteristics of the research problem, its interpretation and its relationship with the various economic variables associated with it. The research reached the following results:- The continuous financing of the state budget deficit during the crisis period by borrowing from the central bank led to negative economic and social effects, the most prominent of which were the increase in the flow of the monetary mass, the high rates of inflation, the decrease in the exchange rate of the Syrian pound, and the raising of interest rates in banks ... etc.- Financing the state budget in Syria through the issuance of government securities will be one of the most important methods of financing the reconstruction process in Syria, given its expected significant positive effects on the Syrian economy.- The experience of using government securities to finance the state’s general budget in Syria is a recent experience, and it is too early to evaluate its results. The success of this experiment will depend on removing all the problems surrounding it, and benefiting from the successful experiences of other countries in this field.